CT findings associated with blastic plasmacytoid dendritic cell neoplasm: a case report. (July 2016) - Jeong, Daniel; Choi, Jung W; Jeong, Katherine; Sokol, Lubomir
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare hematologic malignancy that is frequently misdiagnosed. We present a case of a 53-year-old man diagnosed with blastic plasmacytoid dendritic cell neoplasm with extensive computed tomography (CT) findings and provide an imaging focused review of this uncommon malignancy.